Dereplication of secondary metabolites from Sophora flavescens using an LC–MS/MS-based molecular networking strategy - Hua Wang; Hui Ding (Scientific Reports)
Abstract A dereplication strategy was developed for the screening of secondary metabolites from Sophora flavescens. The strategy consisted of 4 procedures. First, the extract of the Sophora flavescens root was subjected to LC–MS/MS analysis with both data-independent acquisition (DIA) mode and data-dependent acquisition (DDA) mode. Then the DIA results were used to construct a molecular networking (MN) according to the GNPS workflow and consequently obtain annotations. In parallel, the DDA results were projected to both MN analysis and direct databases matching to obtain annotations. Finally, the isomers were discriminated and annotated by their extracted ion chromatogram. Through the combination of these approaches, a total of 51 compounds were annotated and dereplicated in the Sophora flavescens samples. The annotation results showed DIA and DDA approach are complementary to each other. MN on GNPS can overcome the challenges of trace compound identification compared to direct DB matching. This strategy provides a powerful tool for the dereplication study in plant chemistry.